Influence of Climate Warming on Arctic Mammals ? New Insights from Ancient DNA Studies of the Collared Lemming Dicrostonyx torquatus - Doris Nagel (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (PLoS ONE, 2010)
The abstract is available here: https://uscholar.univie.ac.at/o:245579 The abstract is available here: https://uscholar.univie.ac.at/o:245579